Galeri Seni Tari dengan Pendekatan Arsitektur Ikonik di Polewali Mandar - Huzain, Putra; Said, Ratriana; Alfiah, Alfiah (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2022)
Abstract_ Polewali Mandar is one of the districts in Indonesia that has a variety of dance arts. It is believed to be the center of art and culture. In 2019 Polewali Mandar hosted the Polewali Mandar International Folk and Art Festival (PIFAF) to promote the arts and culture of the people in West Sulawesi (Sulbar) to foreign tourists, who since 2016 hosted the event. Because of this, it was thought to plan an Art Gallery in Polewali Mandar where people can study, demonstrate, maintain and develop art as the times go on. In the design process, an Art Gallery is planned that can show the expression of art. Keywords: Gallery of Dance Art: Iconic Architecture; Polewali Mandar.